Characterization of three chalcone synthase-like genes from apple (Malus x domestica Borkh.). (August 2017) - Yahyaa, Mosaab; Ali, Samah; Davidovich-Rikanati, Rachel; Ibdah, Muhammad; Shachtier, Alona; Eyal, Yoram; Lewinsohn, Efraim; Ibdah, Mwafaq
Abstract: Apple ( Malus x domestica Brokh.) is a widely cultivated deciduous tree species of significant economic importance. Apple leaves accumulate high levels of flavonoids and dihydrochalcones, and their formation is dependent on enzymes of the chalcone synthase family. Three CHS genes were cloned from apple leaves and expressed in Escherichia coli. The encoded recombinant enzymes were purified and functionally characterized. In-vitro activity assays indicated that MdCHS1, MdCHS2 and MdCHS3 code for proteins exhibiting polyketide synthase activity that accepted either p -dihydrocoumaroyl-CoA, p -coumaroyl-CoA, or cinnamoyl-CoA as starter CoA substrates in the presence of malonyl-CoA, leading to production of phloretin, naringenin chalcone, and pinocembrin chalcone. MdCHS3 coded a chalcone-dihydrochalcone synthase enzyme with narrower substrate specificity than the previous ones. The apparent Km values of MdCHS3 for p -dihydrocoumaryl-CoA and p -coumaryl-CoA were both 5.0 μM. Expression analyses of MdCHS genes varied according to tissue type. MdCHS1, MdCHS2 and MdCHS3 expression levels were associated with the levels of phloretin accumulate in the respective tissues. Graphical abstract: Image 1 Highlights: Three chalcone synthases were identified and characterized from apple leaves. MdCHS1, MdCHS2 and MdCHS3 catalyzing the formation of phloretin, naringenin chalcone, and pinocembrin chalcone. MdCHS3 has a narrow substrate specificity than MdCHS1 and MdCHS2. Expression analysis suggests that the enzymes may play a crucial role in phloretin dihydrochalcone and flavonoid biosynthesis.